Perceptions and Hesitancy of Covid-19 Vaccination among the Elderly: A Qualitative Study - Bayu Lorensho Lian; Violin Irene Ninef; Otniel Blegur (Jurnal Vocational Nursing Sciences (VNUS), 2023)
Background: Corona Virus Disease (COVID-19) is a new type of virus that attacks the body's immunity and can cause death. Vaccination for COVID-19 is the government's effort to break the chain of transmission of COVID-19. Perception can be formed from differences in one's perspective on a particular object by using the senses that are owned either directly or indirectly.Objective: The purpose of this study was to find out the perceptions and doubts of the elderly about the covid-19 vaccine in the Oeteta Village environment. Research methods: This study uses a qualitative method with a phenomenological approach. Data collection is done by using techniquespurposive Sampling is a technique for determining participants based on certain criteria or considerations. The data analysis used in the descriptive phenomenological study uses a strategy by Colaizzi. Results: The results of the study of 6 participants showed that in analyzing the perceptions and doubts of COVID-19 vaccination in the elderly in Oeteta Village, namely participant knowledge of vaccination, participant experience regarding vaccination, participants' feelings about vaccination, information obtained about vaccination, and participants' expectations regarding vaccinations, Therefore, the village government and health workers are making important efforts to increase the perception of the elderly community about receiving the COVID-19 vaccination by conducting socialization regarding the safety, effectiveness of the vaccine, benefits, side effects, how to overcome them, and when to give the COVID-19 vaccination.